Impact of Disturbing Factors on Cooperation in Logistics Outsourcing Performance: The Empirical Model - Križman, Andreja; Ogorelc, Anton (Promet - Traffic&Transportation, 2010)
The purpose of this paper is to present the research results of a study conducted in the Slovene logistics market of conflicts and opportunism as disturbing factors while examining their impact on cooperation in logistics outsourcing performance. Relationship variables are proposed that directly or indirectly affect logistics performance and conceptualize the hypotheses based on causal linkages for the constructs. On the basis of extant literature and new argumentations that are derived from in-depth interviews of logistics experts, including providers and customers, the measurement and structural models are empirically analyzed. Existing measurement scales for the constructs are slightly modified for this analysis. Purification testing and measurement for validity and reliability are performed. Multivariate statistical methods are utilized and hypotheses are tested. The results show that conflicts have a significantly negative impact on cooperation between customers and logistics service providers (LSPs), while opportunism does not play an important role in these relationships. The observed antecedents of logistics outsourcing performance in the model account for 58.4% of the variance of the goal achievement and 36.5% of the variance of the exceeded goal. KEYWORDS: logistics outsourcing performance; logistics customer–provider relationships; conflicts and cooperation in logistics outsourcing; PLS path modelling